2003
DOI: 10.1007/s11738-003-0017-0
|View full text |Cite
|
Sign up to set email alerts
|

Differential antioxidant enzyme and thiol responses of tolerant and non-tolerant clones of Chloris barbata to cadmium-stress

Abstract: Key words: a n t i o x i d a n t s , c a d m i u m , Chloris barbata, metal-tolerance, stress-response Abstract Tolerant and non-tolerant clones of Chloris barbara Sw. obtained, respectively, from an erstwhile mercury contaminated solid waste dump site near a chloralkali plant and a non-contaminated (control) site were subjected to cadmium-stress by growing the rooted cuttings in water containing CdSO4, 13 and 130 ~tM. Differences between the two clones in their response to cadmimn-stress were noted in root gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
2
3
0
Order By: Relevance
“…This is in accordance with the results obtained by Wu et al (2003) that Cd-stress induced a concentration and gene type dependent oxidative stress response and changes in barley leaf blades characterised by the alteration pattern of antioxidative enzymes superoxide dismutase (SOD) and peroxidase (POD). The increase of total polyphenols content as a response to Cd-stress is similar, as Baisakhi et al (2003) determined in the tolerant clone of Chloris barbata Sw. in protein-thiol level. As Chai et al (2003) found in the French bean (Phaseolus vulgaris), the expression of stress-related genes as PvSR2 can enhance the Cd tolerance, esp.…”
Section: Resultssupporting
confidence: 78%
“…This is in accordance with the results obtained by Wu et al (2003) that Cd-stress induced a concentration and gene type dependent oxidative stress response and changes in barley leaf blades characterised by the alteration pattern of antioxidative enzymes superoxide dismutase (SOD) and peroxidase (POD). The increase of total polyphenols content as a response to Cd-stress is similar, as Baisakhi et al (2003) determined in the tolerant clone of Chloris barbata Sw. in protein-thiol level. As Chai et al (2003) found in the French bean (Phaseolus vulgaris), the expression of stress-related genes as PvSR2 can enhance the Cd tolerance, esp.…”
Section: Resultssupporting
confidence: 78%
“…Although the oxidative stress profiles were unaffected in Cdtolerant callus acclimatized to grown under high Cd concentration, these were significantly enhanced both in terms of lipid peroxidation and protein oxidation in callus exposed to Cd shock. The differential expression of lipid peroxidation between Cd-tolerant/resistant and -non-tolerant/ susceptible clones has also been reported in Chloros barbata (Baisakhi et al 2003) and in Salix viminalis (Landberg and Greger 2002). However, the present results could constitute initial evidence that Cd-acclimatized cells were more effective in coping with Cd-induced oxidative damage.…”
Section: Discussionsupporting
confidence: 70%
“…Similarly, high increases in the level of TT and NPT were observed in maize plants treated with isoproturon, but thiols were elevated only during the first few days and by low doses of the tested compound [38]. In contrast, the content of NPT in non-tolerant clone of Chloris barbata L. increased under cadmium stress [39].…”
Section: Discussionmentioning
confidence: 99%